Electrical control of deep NV centers in diamond by means of sub-superficial graphitic micro-electrodes. (March 2017) - Forneris, J.; Ditalia Tchernij, S.; Tengattini, A.; Enrico, E.; Grilj, V.; Skukan, N.; Amato, G.; Boarino, L.; Jakšić, M.; Olivero, P.
Abstract: The control of the charge state of nitrogen-vacancy (NV) centers in diamond is of primary importance for the stabilization of their quantum-optical properties, in applications ranging from quantum sensing to quantum computing. In this work buried current-injecting graphitic micro-electrodes were fabricated in bulk diamond by means of a 6 MeV C 3+ scanning micro-beam. The electrodes were exploited to control the variation in the relative population of the negative (NV − ) and neutral (NV 0 ) charge states of a sub-superficial NV centers ensemble located in the inter-electrode gap region. Photoluminescence spectra exhibited an electrically-induced increase up to 40% in the NV − population at the expense of the NV 0 charge state, with a linear dependence from the injected current at applied biases smaller than 350 V, and was interpreted as the result of electron trapping at NV sites. An abrupt current increase at ∼350 V bias resulted in a strong electroluminescence from the NV 0 centers, in addition to two spectrally sharp emission lines at 563.5 nm and 580 nm, not visible under optical excitation and attributed to self-interstitial defects. These results disclose new possibilities in the electrical control of the charge state of NV centers located in the diamond bulk, which are characterized by longer spin coherence times. Graphical abstract: